NOTAS PARA ANÁLISE DO CAPITALISMO CONTEMPORÂNEO A PARTIR DE LÊNIN E CHESNAIS - Cláudia Alves Durans; Marcos Antônio Silva do Nascimento (Revista de Políticas Públicas, 2018)
This article aims to analyze the transformations that monopoly capitalism has been going through since the end of the 19th century as a way of coping with the crises that are inherent to them. From the relation between productive capital and financial capital, the way in which capital has been organizing and reorganizing for the valorization of socially produced wealth. We make this analysis from two authors: Lenin and Chesnais, having as reference the elaborations of Marx. They lived in different contexts of the intensification of the tendency of concentration and centralization of capitals, resulting in the overexploitation of labor and imperialist nations over the others. Finally, it notes the importance and interest in studying for the understanding of contemporary capitalism and the possibilities of combating it.